2007
DOI: 10.1063/1.2743972
|View full text |Cite
|
Sign up to set email alerts
|

Energies of the first row atoms from quantum Monte Carlo

Abstract: All-electron variational and diffusion quantum Monte Carlo calculations of the ground state energies of the first row atoms (from Li to Ne) are reported. The authors use trial wave functions of four types: single-determinant Slater-Jastrow wave functions, multideterminant Slater-Jastrow wave functions, single-determinant Slater-Jastrow wave functions with backflow transformations, and multideterminant Slater-Jastrow wave functions with backflow transformations. At the diffusion quantum Monte Carlo level and us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 39 publications
7
90
2
Order By: Relevance
“…We tested optimization of the single-particle orbitals for N, O and F, but found this to have a negligible effect, in agreement with previous atomic studies 15,16 .…”
Section: Optimizationsupporting
confidence: 85%
See 2 more Smart Citations
“…We tested optimization of the single-particle orbitals for N, O and F, but found this to have a negligible effect, in agreement with previous atomic studies 15,16 .…”
Section: Optimizationsupporting
confidence: 85%
“…13 and 14, our current implementation is more effective and robust. For example, Brown et al 15 were unable to lower the VMC energy of Ne using a multi-determinant expansion, which was easily achieved in the present study. The present optimization strategy is significantly different as we use MAD minimization to first optimize the non-linear parameters at each stage.…”
Section: A Atomic and Ionic Energiesmentioning
confidence: 65%
See 1 more Smart Citation
“…These observations let to further studies of backflow combined with the wave functions that have the minimal number of nodal cells -an important topological property associated with ground state wave functions. 36,37,38,39 One of the successes of this scheme are the very recent results of Brown et al 53 obtained from backflow correlated CI-Jastrow wave functions applied to first row all-electron atoms. In this study, we further test the limits of the backflow correlations to decrease the fixed node errors of the CI-Jastrow wave functions and, for the first time, also include backflow into the pfaffian-Jastrow pairing wave functions.…”
Section: B Carbon Atom and Dimermentioning
confidence: 99%
“…In this work, we will show that quantum Monte Carlo (QMC) is an alternative efficient approach to achieve or surpass such accuracy in benzene crystals, as we previously demonstrated for the benzene dimer. 16 Quantum Monte Carlo (QMC), which approximately solves the electronic Schrödinger equation stochastically, 17 can yield highly accurate energies for atoms, 18,19 molecules, [20][21][22] and crystals. [23][24][25] Previous studies have shown that diffusion quantum Monte Carlo (DMC) can provide accurate energies for noncovalent interactions systems.…”
Section: Introductionmentioning
confidence: 99%